Anorexia nervosa in children and adolescents: an early detection of risk factors - Elena Bozzola; Sarah Barni; Maria Rosaria Marchili; Romie Hellmann; Emanuela Del Giudice; Giampaolo De Luca; Vita Cupertino; for the Italian Pediatric Society Adolescent Study Group (BMC, 2024)
Abstract The incidence of eating disorders in children, mainly of anorexia nervosa, is dramatically increased in the last years. A timely identification of the disease is associated with higher rates of recovery. Aim of the work is to underline signs and symptoms that can be used to an early detection of anorexia nervosa in the pediatric age. A scoping review has been conducted by The Italian Pediatric Society Adolescent Study Group according to the PRISMA Extension guidelines for Scoping Reviews, using the search term "anorexia nervosa" and the following filters "review", "systematic review", "age 0-18", "last 4 years". The strategy search produced 657 studies, of which 52 were included in this revision. Screening and red flags were discussed in 23 reports, genetics in 12, neurological pathways in 11, environmental factors in 10, and gut microbiota in 7. An accurate physiological and pathological anamnesis, physical and psychological examination, including the body perception, should be taken in account as well as the presence of co-morbidities, including chronic functional abdominal pain and autoimmune/autoinflammatory diseases. Evidence suggests the role of familiar predisposition as well as of neurological morphology and pathway in anorexia nervosa development. Gut microbiota has also been included among possible risk factor for developing anorexia nervosa due to a complex direct and indirect interactions between gut and brain. The Italian Pediatric Society Adolescent Study Group suggests performing an accurate familial and personal anamnesis, including psychological evaluation as well as a physical exam including auxological parameters as a screening tool during pediatric checks to better explore the risk of developing anorexia nervosa.